2021
DOI: 10.1093/jmcb/mjab018
|View full text |Cite|
|
Sign up to set email alerts
|

Fatty acid oxidation and autophagy promote endoxifen resistance and counter the effect of AKT inhibition in ER-positive breast cancer cells

Abstract: Tamoxifen (TAM) is the first-line endocrine therapy for estrogen receptor-positive (ER+) breast cancer (BC). However, acquired resistance occurs in ∼50% cases. Meanwhile, although the PI3K/AKT/mTOR pathway is a viable target for treatment of endocrine therapy-refractory patients, complex signaling feedback loops exist, which can counter the effectiveness of inhibitors of this pathway. Here, we analyzed signaling pathways and metabolism in ER+ MCF7 BC cell line and their TAM-resistant derivatives that are co-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…AKT is the main signaling pathway essentially transmitting mitogen and growth factors. Besides, AKT inhibits BAD protein via phosphorylation and represses induced apoptosis [10,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKT is the main signaling pathway essentially transmitting mitogen and growth factors. Besides, AKT inhibits BAD protein via phosphorylation and represses induced apoptosis [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that stress causes cell death including apoptosis and autophagy and leads to activation of AMPK and suppressor of mTOR [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The AMPK activation promoted activation of AKT, while inhibition of AKT feedback suppressed the expression AMPK. AMPK additionally increased CPT1, which finally lead to the increase in fatty acid oxidation [138] . The molecular mechanism of sorafenib's antitumoral activity in BC is impairment of glucose metabolism by sustained activation of AMPK [147] .…”
Section: Ampk Pathwaymentioning
confidence: 98%
“…1 ). In BC tumor and cell lines, the expression of CPT1A increased in ER-positive compared with ER-negative [137] via upregulating expression of ERRα and peroxisome proliferator activated receptor gamma coactivator 1 (PGC-1) β by activation of AMPK [138] , finally countering the effect of AKT inhibition. CPT1A overexpression significantly attenuated the proliferation in MDA-MB231 BC cells when compared with basal expression control.…”
Section: Fatty Acids Metabolismmentioning
confidence: 99%
“…This idea is supported by studies from other solid tumors where CPT1A expression was associated with metastatic ability, EMT and drug resistant phenotype and its inhibition re-sensitized resistant cells to radiation, hormone therapy and/or and chemo-therapy [ 180 , 181 , 241 , 242 , 243 , 244 , 245 , 246 ]. Mechanistically, endocrine-resistant cells have been shown to express high levels of ERRα/PGC-1β and increased expression of a number of target genes, including CPT1A, which has been shown to increase FAO [ 247 ]. Likewise, CD36, which facilitates cellular import of fatty acids from the micro-environment, is upregulated in endocrine-resistant tumors and cell lines.…”
Section: Metabolism In Therapeutic Resistance and Novel Clinical Opportunitiesmentioning
confidence: 99%